STUDY OF TYPES OF FENCE PLANTS AND ITS BENEFITS FOR HEALTH - Fajriana, Nurul; Khatimah, Husnul (Jurnal Biologi Sains dan Kependidikan, 2023)
Various types of plants provide many benefits for humans, including several types of plants that can be used as ornamental plants and hedges. Not only functioning as a barrier, hedges also have social functions as medicine, ecological functions, and aesthetic functions. This study aims to determine the types of plants that can be used as a fence and their health benefits. The research method used is descriptive qualitative method. Data was collected using the method of literature study/literature review both online and offline. Types of plants that can generally be used as hedges are boxwood, roses, fir fans, butter flowers, bamboo, ashoka, ferns, hibiscus, red shoots, paper flowers, and mother-in-law's tongue. These types of plants contain various phytochemical compounds that are very beneficial for health, including anti-diabetic, anti-cancer because they are rich in anti-oxidants, anti-inflammatory, anti-bacterial and viral, anti-fungal, anti-ulcer, anti-depressant, analgesic, etc.